2023
DOI: 10.1021/acsami.3c06905
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhanced Antibacterial and Antifouling Behavior of Three-Dimensional Porous Cu2O Nanoparticles Functionalized by an Organic–Inorganic Hybrid Matrix

Abstract: Cu 2 O is currently an important protective material for domestic engineering and equipment used to exploit marine resources. Cu + is considered to have more effective antibacterial and antifouling activities than Cu 2+ . However, disproportionation of Cu + in the natural environment leads to its reduced bioavailability and weakened reactivity. Novel and functionalized Cu 2 O composites could enable efficient and environmentally friendly applications of Cu + . To this end, a series of threedimensional porous C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the Cu 2 O spectrum showed that the strong characteristic peaks symbolizing Cu + 2p 3/2 and Cu + 2p 1/2 were located at 932.38 and 952.38 eV, whereas the characteristic peaks symbolizing Cu ion 2p 3/2 and Cu ion 2p 1/2 were located at 934.68 and 955.08 eV, respectively [ 39 ]. As a comparison, both peak positions symbolizing Cu + in Cu 2 O@rGO redshifted, which indicates that there is an interaction between rGO and Cu 2 O [ 40 ]. Based on previous studies, a reasonable explanation is that Cu + utilized oxygen-containing functional groups of rGO as targets for the in situ growth of Cu 2 O [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Cu 2 O spectrum showed that the strong characteristic peaks symbolizing Cu + 2p 3/2 and Cu + 2p 1/2 were located at 932.38 and 952.38 eV, whereas the characteristic peaks symbolizing Cu ion 2p 3/2 and Cu ion 2p 1/2 were located at 934.68 and 955.08 eV, respectively [ 39 ]. As a comparison, both peak positions symbolizing Cu + in Cu 2 O@rGO redshifted, which indicates that there is an interaction between rGO and Cu 2 O [ 40 ]. Based on previous studies, a reasonable explanation is that Cu + utilized oxygen-containing functional groups of rGO as targets for the in situ growth of Cu 2 O [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The initial phases of biofouling layer development involve the irreversible colonization and differentiation of bacteria on the substrate surface . Consequently, it is recommended to assess the antibacterial properties of samples prior to investigating their antibiofouling characteristics.…”
Section: Results and Discussionmentioning
confidence: 99%